Magnetothermal transport in ultraclean single crystals of Kitaev magnet α-RuCl3 - Y. Xing; R. Namba; K. Imamura; K. Ishihara; S. Suetsugu; T. Asaba; K. Hashimoto; T. Shibauchi; Y. Matsuda; Y. Kasahara (npj Quantum Materials)
Abstract The layered honeycomb magnet α-RuCl3 has emerged as a promising candidate for realizing a Kitaev quantum spin liquid. Previous studies have reported oscillation-like anomalies in the longitudinal thermal conductivity and half-integer quantized thermal Hall conductivity above the antiferromagnetic critical field H c , generating significant interest. However, the origins of these phenomena remain contentious due to strong sample dependence. Here we re-examine the magnetothermal transport properties using recently available ultra-pure α-RuCl3 single crystals to further elucidate potential signatures of the spin liquid state. Our findings reveal that while anomalies in thermal conductivity above H c persist even in ultraclean crystals, their magnitude is significantly attenuated, contrary to the quantum oscillations hypothesis. This suggests that the anomalies are likely attributable to localized stacking faults inadvertently introduced during magnetothermal transport measurements. The thermal Hall conductivity exhibits a half-quantized plateau, albeit with a narrower width than previously reported. This width reduction can be understood through two distinct mechanisms: sample-dependent magnetic critical fields that influence the lower boundary of the plateau region, and the decoupling between chiral Majorana edge currents and phononic thermal transport that determines the upper boundary. These results indicate that structural imperfections exert a substantial influence on both the oscillation-like anomalies and quantization effects observed in magnetothermal transport measurements of α-RuCl3.